VEGF signalling enhances lesion burden in KRIT1 deficient mice - DiStefano, Peter V. (J Cell Mol Med, 2019)
The exact molecular mechanisms underlying CCM pathogenesis remain a complicated and controversial topic. Our previous work illustrated an important VEGF signalling loop in KRIT1 depleted endothelial cells. As VEGF is a major mediator of many vascular pathologies, we asked whether the increased VEGF signalling downstream of KRIT1 depletion was involved in CCM formation. Using an inducible KRIT1 endothelial‐specific knockout mouse that models CCM, we show that VEGFR2 activation plays a role in CCM pathogenesis in mice. Inhibition of VEGFR2 using a specific inhibitor, SU5416, significantly decreased the number of lesions formed and slightly lowered the average lesion size. Notably, VEGFR2 inhibition also decreased the appearance of lesion haemorrhage as denoted by the presence of free iron in adjacent tissues. The presence of free iron correlated with increased microvessel permeability in both skeletal muscle and brain, which was completely reversed by SU5416 treatment. Finally, we show that VEGFR2 activation is a common downstream consequence of KRIT1, CCM2 and CCM3 loss of function, though the mechanism by which VEGFR2 activation occurs likely varies. Thus, our study clearly shows that VEGFR2 activation downstream of KRIT1 depletion enhances the severity of CCM formation in mice, and suggests that targeting VEGF signalling may be a potential future therapy for CCM.